Blast-induced brain injury in rats leads to transient vestibulomotor deficits and persistent orofacial pain. (6th December 2018) - Studlack, Paige E.; Keledjian, Kaspar; Farooq, Tayyiaba; Akintola, Titilola; Gerzanich, Volodymyr; Simard, J. Marc; Keller, Asaf
ABSTRACT: Blast-induced traumatic brain injury (blast-TBI) is associated with vestibulomotor dysfunction, persistent post-traumatic headaches and post-traumatic stress disorder, requiring extensive treatments and reducing quality-of-life. Treatment and prevention of these devastating outcomes require an understanding of their underlying pathophysiology through studies that take advantage of animal models. Here, we report that cranium-directed blast-TBI in rats results in signs of pain that last at least 8 weeks after injury. These occur without significantly elevated behavioural markers of anxiety-like conditions and are not associated with glial up-regulation in sensory thalamic nuclei. These injuries also produce transient vestibulomotor abnormalities that resolve within 3 weeks of injury. Thus, blast-TBI in rats recapitulates aspects of the human condition.